2010
DOI: 10.1088/0967-3334/32/2/003
|View full text |Cite
|
Sign up to set email alerts
|

Chest tcpO2changes during constant-load treadmill walking tests in patients with claudication

Abstract: Changes in chest transcutaneous-pO 2 at rest ( tcpO 2 ) mimic absolute changes in arterial-pO 2 during moderate exercise, although the absolute starting values may dramatically differ. We retrospectively studied 485 patients (group 1), prospectively studied 292 new patients (group 2) and estimated the intra-test and the test-retest reproducibility of tcpO 2 during constant-load treadmill tests: 3.2 km h −1 , 10% grade, using the cross correlation technique. Patients were classified into groups according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 22 publications
1
31
1
Order By: Relevance
“…As previously discussed, systemic arterial oxygen pressure influences absolute tcPO2, and changes throughout exercise in arterial partial oxygen pressure may be estimated by changes in tcPO2. 7,8 Assuming that the C and D profiles reflect exercise-induced hypoxemia, we hypothesized that systemic hypoxemia may worsen the tissue oxygen imbalance at exercise and result in a non-vascular contribution to walking limitation. Although the relationship between abnormal chest profile and cardiorespiratory disease is not yet established, we generally refer such patients for cardiopulmonary investigations and repeat Ex-tcPO2 after treatment of frequently detected cardiopulmonary disease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously discussed, systemic arterial oxygen pressure influences absolute tcPO2, and changes throughout exercise in arterial partial oxygen pressure may be estimated by changes in tcPO2. 7,8 Assuming that the C and D profiles reflect exercise-induced hypoxemia, we hypothesized that systemic hypoxemia may worsen the tissue oxygen imbalance at exercise and result in a non-vascular contribution to walking limitation. Although the relationship between abnormal chest profile and cardiorespiratory disease is not yet established, we generally refer such patients for cardiopulmonary investigations and repeat Ex-tcPO2 after treatment of frequently detected cardiopulmonary disease.…”
Section: Resultsmentioning
confidence: 99%
“…9 The profiles A or B were considered normal, while classification into profiles C or D indicated abnormal systemic oxygenation during exercise (Figure 1). 8 In patients with C or D profiles, it is assumed that respiratory limitation might impair walking ability and limit exercise before a measurable significant ischemia occurs at the limb level. years, and 81% were male.…”
Section: Chest-tcpo2 Change Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of exercise transcutaneous pO 2 has recently gained interest in claudication, specifically in case of atypical claudication or claudication of questionable vascular origin [3][5]. We recently reported that, in patients with claudication and assumed peripheral artery disease referred for constant-load walking tests, the transcutaneous pO 2 changes while walking could be automatically classified into 4 empirically predefined types [6]. Two of them mimic the expected physiological walking-induced increase in arterial pO 2 (type A & B).…”
Section: Introductionmentioning
confidence: 99%
“…13 We showed that Ex-tcPO2 also accounts for eventual systemic arterial oxygen pressure changes through the use of the chest electrode. 14 Since 2000 we have progressively integrated Ex-tcPO2 in our diagnostic routine of claudication as a tool to argue for the vascular origin of exercise-induced pain, specifically at the proximal level. Ex-tcPO2 was initially performed in highly selected patients for whom usual techniques and/or post-exercise ABI were negative or impossible.…”
mentioning
confidence: 99%